2010
DOI: 10.2119/molmed.2010.00057
|View full text |Cite
|
Sign up to set email alerts
|

Altered mRNA Expression of Telomere-Associated Genes in Monoclonal Gammopathy of Undetermined Significance and Multiple Myeloma

Abstract: In this study, we explored changes in the expression of the telomere maintenance genes, TRF1, TRF2 and TANK1 in patients with monoclonal gammopathy of undetermined significance (MGUS) and multiple myeloma (MM). Results were correlated with human telomerase reverse transcriptase (hTERT ) expression, telomere length (TL) and clinicopathological characteristics. Bone marrow (BM) samples from 132 patients, 64 with MGUS and 68 with MM, were studied. Real-time quantitative reverse transcription-polymerase chain reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
16
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 36 publications
8
16
0
1
Order By: Relevance
“…The expression profile of shelterin genes in plasma cell disorders have been extensively studied by our group (Table 1) (94,96,97). Our findings showed increased expression of shelterin components in MM compared to MGUS.…”
Section: Plasma Cell Disorderssupporting
confidence: 56%
See 1 more Smart Citation
“…The expression profile of shelterin genes in plasma cell disorders have been extensively studied by our group (Table 1) (94,96,97). Our findings showed increased expression of shelterin components in MM compared to MGUS.…”
Section: Plasma Cell Disorderssupporting
confidence: 56%
“…However, telomerase levels were not elevated in MGUS. As shown in Table 1, studies of our group have found increased expression levels of TERT, in MM as well as in MGUS, providing the first evidence of a modification in the expression of telomerase gene in these entities (94). Interestingly, in both pathologies a similar pattern of TERT expression was observed, in which patients displaying the highest telomerase transcription levels had the shortest TLs.…”
Section: Plasma Cell Disorderssupporting
confidence: 55%
“…To confirm the results from the microarray analysis we analysed gene expression by quantitative PCR. We used reverse transcribed RNA extracted from five controls of PBMC from healthy donors, eight HMCLs, six samples of CD138 + malignant plasma cells and CD138 − plasma cells from patients with MM, two hESCs and one iPSCs, and measured expression levels for all sixteen deregulated genes plus four additional genes involved in telomere maintenance ( TRF1 , TRF2 , TNKS and hTERT ) . Log 2 of the normalized microarrays ratio values were compared with log 2 ratio values from qPCR experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Total RNA was extracted from mononuclear cells isolated from BM samples of patients, as previously reported [ 28 ]. The cDNA synthesis was performed in a final volume of 20 μl, containing 1μg of the total RNA, for 10 minutes at 95°C, for 60 minutes at 37°C and 10 minutes at 95°C to inactive the enzyme.…”
Section: Methodsmentioning
confidence: 99%